2020
DOI: 10.3390/w12030851
|View full text |Cite
|
Sign up to set email alerts
|

Limnological Quality: Seasonality Assessment and Potential for Contamination of the Pindaré River Watershed, Pre-Amazon Region, Brazil

Abstract: Watersheds are defined as a set of lands where water drainage occurs through rivers and their tributaries. A large quantity of water resources exist in the state of Maranhão, Brazil, where rivers and their basins must meet environmental quality standards defined by the limits set out in national environmental council (CONAMA) legislation 357/05 for physicochemical and microbiological parameters, including parasites. Multivariate statistical techniques were applied to study the temporal and spatial variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…Except for color, turbidity, and pH, the mean range of EC, temperature, and TDS fell within the WHO guidelines in the dry and rainy months along the Mara River and its tributaries. Similar findings were reported by Fawaz et al (2013) and Muniz et al (2020), who concluded that it was probably attributed to higher ion dilution in water.…”
Section: Physicochemical Parameterssupporting
confidence: 90%
“…Except for color, turbidity, and pH, the mean range of EC, temperature, and TDS fell within the WHO guidelines in the dry and rainy months along the Mara River and its tributaries. Similar findings were reported by Fawaz et al (2013) and Muniz et al (2020), who concluded that it was probably attributed to higher ion dilution in water.…”
Section: Physicochemical Parameterssupporting
confidence: 90%
“…Water contained fecal contamination indicators that were critical for determining the quality of the water. Total coliforms and E. coli were the most extensively used bacteriological assays to detect harmful bacteria in animal and human feces [71]. In this study, the highest total coliforms and E. coli in the dry season were 1,296,125 MPN/100 mL and 183,500 MPN/100 mL, respectively.…”
Section: Temporal Analysis Of the Opak Sub-watershed's Water Qualitymentioning
confidence: 66%
“…Similar results were acquired by Hulyar and Altug (2020) who stated that pH values and temperature of Cırpıcı River (Istanbul, Turkey) and its flowing areas recorded between 6.0-8.38 and 10.3-29.5ºC. The other study in Pindare River (Brazil) predicated that pH, temperature, TDS, and EC values in the three sampling points in the dry season were 7.06-8.13; 24-27°C; 140.66-185 mg/L and 213-363.33 µS/cm, respectively (Muniz et al, 2020).…”
Section: Resultsmentioning
confidence: 90%